The molecular mechanisms that determine different degrees of polyphagy in the Bemisia tabaci species complex. (20th November 2020) - Malka, Osnat; Feldmesser, Ester; van Brunschot, Sharon; Santos‐Garcia, Diego; Han, Wen‐Hao; Seal, Susan; Colvin, John; Morin, Shai
Abstract: The whitefly Bemisia tabaci is a closely related group of >35 cryptic species that feed on the phloem sap of a broad range of host plants. Species in the complex differ in their host‐range breadth, but the mechanisms involved remain poorly understood. We investigated, therefore, how six different B. tabaci species cope with the environmental unpredictability presented by a set of four common and novel host plants. Behavioral studies indicated large differences in performances on the four hosts and putative specialization of one of the species to cassava plants. Transcriptomic analyses revealed two main insights. First, a large set of genes involved in metabolism (>85%) showed differences in expression between the six species, and each species could be characterized by its own unique expression pattern of metabolic genes. However, within species, these genes were constitutively expressed, with a low level of environmental responsiveness (i.e., to host change). Second, within each species, sets of genes mainly associated with the super‐pathways "environmental information processing" and "organismal systems" responded to the host switching events. These included genes encoding for proteins involved in sugar homeostasis, signal transduction, membrane transport, and immune, endocrine, sensory and digestive responses. Our findings suggested that the six B. tabaci species can be divided into four performance/transcriptomic "Types" and that polyphagy can be achieved in multiple ways. However, polyphagy level is determined by the specific identity of the metabolic genes/pathways that are enriched and overexpressed in each species (the species' individual metabolic "tool kit").